A new result on robust H∞ control for uncertain time‐delay singular systems via sliding mode control. (21st May 2016) - Liu, Zhen; Gao, Cunchen
Abstract : This article is devoted to designing linear sliding surface and adaptive sliding mode controller for a class of singular time‐delay systems with parametric uncertainties and external disturbance. In terms of linear matrix inequalities (LMIs), a sufficient criteria ofH∞ performance, and admissibility for considered sliding motion restricted to linear sliding surface is achieved, and the controller which guarantees the finite‐time reachability of the predesigned sliding surface is then developed, respectively. Finally, three examples show the effectiveness of the proposed result. © 2016 Wiley Periodicals, Inc. Complexity 21: 165–177, 2016